An Improved Motion JPEG2000 Decoder for Error Concealment of Segmentation Symbol Faults. (12th March 2008) - Zargari Zargari, Farzad Farzad; Hashemi Hashemi, Mahmoud Reza Mahmoud Reza
Abstract : The motion JPEG2000 (MJP2) video coding standard uses intraframe compression and provides practical features such as fast coding, easy editing, and error robustness. Error robustness and concealment are some of the crucial requirements of any decoder in error prone applications. In this paper, a new error concealment method for MJP2 decoder has been proposed. The proposed method exploits the remaining temporal redundancies within the MJP2 coded video sequences for error concealment. The realized MJP2 decoder is able to detect and remove the artifacts produced by highly damaged bit planes that were not detected by the segmentation symbol, one of the error resilience tools in MJP2. Simulation results indicate that the proposed decoder can effectively remove such artifacts in the decoded erroneous MJP2 bit streams and improve the PSNR of the corrupted frames by up to 6.8 dB. An average of 0.2 dB improvement has been observed over a relatively large number of test cases and various error rates.